Speech Enhancement Using Modified Spectral Subtraction Algorithm (International Journal of Engineering and Computer Science, 2015)
The term “Speech Enhancement” refereed as to improve quality or intelligibility of speech signal. Speech signal is often degraded by additive background noise like babble noise, train noise, restaurant noise etc. In such noisy environment listening task is very difficult at the end user. Many times speech enhancement is used for pre processing of speech for computer speech recognition system. This paper presents speech enhancement methods like Spectral Subtraction and Modified Spectral Subtraction to reduce additive background noise. Basically these methods are single channel speech enhancement methods. Here , we have tested the clean wave file and observe the spectrogram for the noisy wave file and effect of existing spectral subtraction and proposed spectral subtraction algorithm on the file.